A Synergistic Vascular Effect of Airborne Particulate Matter and Nickel in a Mouse Model - Ying, Zhekang (Oxford University Press, 2013)
Both epidemiological and empirical studies have indicated that nickel (Ni) may play an important role in PM(2.5) exposure–induced adverse cardiovascular effects. However, the underlying mechanism remains unclear. In the present study, we exposed mice to concentrated ambient PM(2.5) (CAP), Ni, or coexposure to both CAP + Ni in a specially designed whole-body exposure system for a duration of 3 months and investigated their effects on vascular function, oxidative stress, and vascular inflammation. CAP + Ni exposure induced greater endothelial dysfunction compared with CAP or Ni alone. Ni exposure decreased endothelial nitric oxide synthase (eNOS) dimers in the aorta, which was potentiated by coexposure with CAP. CAP alone did not reduce NOS dimers but was more effective than Ni in decreasing phosphorylation of eNOS (S1177) and Akt (T308). Ni had minimal effects on the expression of vascular inflammatory genes but synergized with CAP in marked upregulation of tumor necrosis factor-alpha and monocyte chemotactic protein-1. The effects of Ni on NOS monomer formation in endothelial cells were redox dependent as evidenced by attenuation of effects by Tiron in cultured endothelial cells. Ni synergized with lipopolysaccharide, another bioactive component of CAP in reducing eNOS dimerization in cultured endothelial cells. Ni exposure induces endothelial dysfunction through oxidative stress-dependent inhibition of eNOS dimerization. Its interaction with other components of CAP may significantly contribute to the adverse cardiovascular effects of CAP exposure.